Impacts of COVID-19 on local sports organizations. Nationwide survey results - Jackman, F.; Way, R.; Le May Doan, C. (2020)
This report outlines the findings of the nationwide Impacts of COVID-19 on Local Sports Organizations survey in Canada that Sport for Life conducted between May 19 and June 5, 2020, based on Sport Calgary's recent survey. The data collected from 1,300 respondents representing nearly 4 million members and more than 56 sports, informs governments of the operational and financial impacts the pandemic has had on sports organizations. These organizations, which represent about 4% of the sport sector across Canada, collectively employ roughly 14,500 employees so their viability could affect more than 350,000 jobs significantly impacting Canada`s unemployment rate. 99% of sport organizations are affected by COVID-19 while 65% of clubs and associations cannot access Canadian emergency funding initiatives. As many as 21% may not recover without emergency support, resulting in less opportunities for sport. We know that this will especially impact lower socio-economic families. 79% of organizations are servicing our youth. Over 50% will be impacted into 2021.4EXECUTIVE SUMMARYThe organizations have a decreased revenue from registration fees, sale of goods, fundraising, sponsorships, as well as numerous other impacts. Most organizations are trying to adjust their fixed and variable operating costs to survive. Summer camps may not run this year as a result of COVID-19, impacting parents` ability to return to work. 30% of the organizations need only a small amount of emergency funding - less than $20,000 - to help them with COVID-19 inflicted challenges. However, others need more support - 31% need $20,000 to $100,000, while 11% need more than $100,000 to maintain operations. In these turbulent times, sport can build communities, break down barriers and develop resilient people. Sport organizations are working hard to provide much needed opportunities for children to thrive and for adults to stay healthy. However, due to COVID-19, they need help. Sport for Life would like to sincerely thank Sport Calgary for allowing us to use and disseminate this survey to local sports organizations nationwide.